Involvement of CXCL1/CXCR2 During Microglia Activation Following Inflammation-Sensitized Hypoxic-Ischemic Brain Injury in Neonatal Rats - Serdar, Meray; Kempe, Karina; Herrmann, Ralf; Picard, Daniel; Remke, Marc; Herz, Josephine; Bendix, Ivo; Felderhoff-Müser, Ursula; Sabir, Hemmen (Frontiers in Neurology, 2020)
Background: Microglia are key mediators of inflammation during perinatal brain injury. As shown experimentally after inflammation-sensitized hypoxic ischemic (HI) brain injury, microglia are activated into a pro-inflammatory status 24 h after HI involving the NLRP3 inflammasome pathway. The chemokine (C-X-C motif) ligand 1 (CXCL1), and its cognate receptor, CXCR2, have been shown to be involved in NLRP3 activation, although their specific role during perinatal brain injury remains unclear. In this study we investigated the involvement of CXCL1/CXCR2 in brain tissue and microglia and brain tissue after inflammation-sensitized HI brain injury of newborn rats. Methods: Seven-day old Wistar rat pups were either injected with vehicle (NaCl 0.9%) or E. coli lipopolysaccharide (LPS), followed by left carotid ligation combined with global hypoxia (8% O2 for 50 min). Pups were randomized into four different treatment groups: (1) Sham group (n=21), (2) LPS only group (n=20), (3) Veh/HI group (n=39) and (4) LPS/HI group (n=42). Twenty-four hours post hypoxia transcriptome and gene expression analysis were performed on ex vivo isolated microglia cells in our model. Additionally protein expression was analyzed in different brain regions at the same time point. Results: Transcriptome analyses showed a significant microglial upregulation of the chemokine CXCL1 and its receptor CXCR2 in the LPS/HI group compared with the other groups. Gene expression analysis showed a significant upregulation of CXCL1 and NLRP3 in microglia cells after inflammation-sensitized hypoxic-ischemic brain injury. Additionally, protein expression of CXCL1 was significantly upregulated in cortex of male pups from the LPS/HI group. Conclusion: These results indicate that the CXCL1/CXCR2 pathway may be involved during pro-inflammatory microglia activation following inflammation-sensitized hypoxic-ischemic brain injury in neonatal rats. This may lead to new treatment options altering CXCR2 activation early after HI brain injury.